Modifications of Grapevine Berry Composition Induced by Main Viral and Fungal Pathogens in a Climate Change Scenario - Rienth, Markus; Vigneron, Nicolas; Walker, Robert P.; Castellarin, Simone Diego; Sweetman, Crystal; Burbidge, Crista A.; Bonghi, Claudio; Famiani, Franco; Darriet, Philippe (Frontiers in Plant Science, 2021)
The grapevine is subject to myriad fungal and viral diseases, which are responsible for important economic losses in the global wine sector every year. These pathogens deteriorate grapevine berry quality either directly via the modulation of fruit metabolic pathways and the production of endogenous compounds associated with bad taste and/or flavor, or indirectly via their impact on vine physiology. The most common and devastating fungal diseases in viticulture are grey mould, downy mildew (DM), and powdery mildew (PM), caused respectively by Botrytis cinerea, Plasmopara viticola, and Erysiphe necator. Whereas B. cinerea mainly infects and deteriorates the ripening fruit directly, deteriorations by DM and PM are mostly indirect via a reduction of photosynthetic leaf area. Nevertheless, mildews can also infect berries at certain developmental stages and directly alter fruit quality via the biosynthesis of unpleasant flavor compounds that impair ultimate wine quality. The grapevine is furthermore host of a wide range of viruses that reduce vine longevity, productivity and berry quality in different ways. The most widespread virus-related diseases that are known nowadays, are Grapevine Leafroll Disease (GLRD), Grapevine Fanleaf Disease (GFLD), and the more recently characterized Grapevine Red Blotch Disease (GRBD). Future climatic conditions are creating a more favorable environment for the proliferation of most virus-insect vectors, so the spread of virus-related diseases is expected to increase in most wine growing regions. However, the impact of climate change on the evolution of fungal disease pressure will be variable and depending on region and pathogen, with mildews remaining certainly the major phytosanitary threat in most regions because their development rate is to a large extent temperature-driven. This paper aims to provide a review of published literature on most important grapevine fungal and viral pathogens and their impact on grape berry physiology and quality. Our overview of the published literature highlights gaps in our understanding of plant-pathogen interactions, which are valuable for conceiving future research programs dealing with different pests and their impacts on grapevine berry quality and metabolism.